Deficiency in the humoral immune response to vaccine rabies virus in domestic dogs prime vaccinated (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The World Health Organization (WHO) and the Office International desEpizooties (OIE) consider as being the reference status of protection againstrabies titers of virus neutralizing antibodies (VNA) = 0.5 IU/mL to maintaina protective immune response in animals. The aim of this study was to evaluate,according to age, race and period of vaccination and blood collection,the immune response in dogs prime vaccinated with rabies cell culture vaccine.Based on request forms, 432 samples of animals received at the PasteurInstitute of Sao Paulo at the period of 2009 to 2011, those receiving a singledose of vaccine by the time of blood collection were analyzed. We evaluatedthe information on age, race and period of vaccination until to blood collection.The evaluation of VNA to rabies virus was performed by Rapid FluorescentInhibition Test (RFFITT). In this study, we considered animals with lessthan 12 months as puppies and with over 12 months as adults. Of total samplesanalyzed, 21.76% (94) had titers lt;0.5 IU/mL and among these, 63 (67.02%)samples were puppies. When considering the interval between administrationof the vaccine and blood collection, 74 (60.63%) samples did not achieveprotective titers in the first six months interval between vaccination and testshowing a window period especially important in puppies. With regard torace, there was no significant variation. It was concluded that the puppies aremore susceptible to infection by rabies virus than adults, proving the need fora second dose of vaccine in the primary vaccination, which would increase thepossibility of a rapid, efficient and lasting immune response.